2008
DOI: 10.1021/ja711018z
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of Bicyclo[2.2.2]octenones Using a Copper-Mediated Oxidative Dearomatization/[4 + 2] Dimerization Cascade

Abstract: The bicyclo[2.2.2]octenone skeleton is found in a number of natural products (Figure 1) including homodimers 1 2 and 2 (aquaticol), 3 and the hetero adduct chamaecypanone C (3). 4 While Diels-Alder cycloaddition of 2,4-cyclohexadienones and ortho-quinols with activated alkenes has frequently been used for the synthesis of bicyclo[2.2.2]octenones, 2,4-cyclohexadienones also have a high propensity to undergo spontaneous [4+2] We first investigated oxidation of the 2,5-disubstituted phenol carvacrol (4) using c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(63 citation statements)
references
References 20 publications
1
58
0
4
Order By: Relevance
“…In all cases, Diels-Alder cycloaddition between o -quinol 4 and dienophiles 9 proceeded in a highly diastereoselective fashion with [4+2] adducts 10a–g isolated in moderate to excellent yields. Structure elucidation of products using 2D NMR experiments or X-ray crystallography confirmed that endo -[4+2] cycloadducts were the predominate products isolated from the reactions, 12 which is in accordance with both experimental results and theoretical calculations in literature that secondary orbital overlap is believed to govern endo -selectivity. 17 Facial selectivity could be explained by either sterics or hyperconjugation effects according to our computational studies ( vide infra ).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…In all cases, Diels-Alder cycloaddition between o -quinol 4 and dienophiles 9 proceeded in a highly diastereoselective fashion with [4+2] adducts 10a–g isolated in moderate to excellent yields. Structure elucidation of products using 2D NMR experiments or X-ray crystallography confirmed that endo -[4+2] cycloadducts were the predominate products isolated from the reactions, 12 which is in accordance with both experimental results and theoretical calculations in literature that secondary orbital overlap is believed to govern endo -selectivity. 17 Facial selectivity could be explained by either sterics or hyperconjugation effects according to our computational studies ( vide infra ).…”
Section: Resultssupporting
confidence: 84%
“…14 Based on UPLC-MS data, reactions showing major peaks in the HPLC trace were scaled up (0.06 mmol, 20 mg substrate) using a SiC chip as passive heating element in a single mode microwave reactor. 12 The results of the reaction screening indicated that dimer 2 was completely consumed in all cases. Of the 57 reactions, 12 afforded products corresponding to [4+2] adducts between the o -quinol and alkene reaction partners, and other reactions afforded product 8 (Scheme 2), likely generated from a dienone-phenol rearrangement of intermediate 4 .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The system could be operated continuously for 20 h without loss of catalyst activity (Scheme 3 c). [74] A related continuous-flow procedure was adopted for the enantioselective synthesis of bicycle- [75] and the microtubule inhibitor (+)-chamaecypanone C. [76] A continuous process was established for the production of 2,2,6,6-tetramethylpiperidin-4-ol over Cu-Cr/g-Al 2 O 3 in a fixedbed reactor (Scheme 4 a). While the selectivity decreased from 98 % at 98 8C to 77 % at 152 8C, it increased from 75 % to 92 % with the increase of hydrogen pressure from 10 bar to 40 bar.…”
Section: Carbonyl Group Hydrogenationmentioning
confidence: 99%
“…[2] Among these, hydroxylative phenol and naphthol dearomative strategies play a pivotal role in metabolite degradation [3] through the formation of the 6-hydroxy-2,4-cyclohexadienone moiety 1, [4] which thus represents a key structural intermediate in the biomimetic total synthesis of natural products, including bacchopetiolone [5] (2), bisorbicillinol [6] (3), sclerotiorin [7] (4), and arianciamycinone [8] (5) (Figure 1). The transformation of phenols and naphthols into the corresponding ortho-quinol products was investigated by using a variety of reagents including peracids, [9] (PhSeO) 2 O, [10] hypervalent iodine compounds, [11] as well as (oxo)-or (peroxo)metal species either in a stoichiometric [12] or catalytic [13] amount. Unfortunately, these methodologies often exhibit low chemo-and regioselectivities due to side-reactions including competitive para oxidation, [11f,13b] overoxidation of alkene functions, [11d] α-ketol rearrangement [12,13a] or phenol homocoupling [11f,12] (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%